Analysing the Evolution of Repetitive Strands in Genomes - Lousado, José (2012)
The analysis of genomes and proteomes of the various organisms allow us to observe its behaviour in the evolution of species. In this study, we focus our attention on a particular aspect of this analysis: the conservation of specific codon and amino acid repetitions in orthologous genes belonging to eukaryotic organisms that are representative of different stages of species evolution. Since it is known that these repeats in humans are the cause of various neurodegenerative diseases, among others, this study help explaining if there is conservation or repression of such repetitions in the specialization process, and if there is any relationship between these repetitions and diseases in advanced live beings.